PELATIHAN PEMBUATAN PROBIOTIK PADA PETANI PEMBUDIDAYA IKAN DESA PEUNAGA PAYA KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Fitria Rahmayanti (Jurnal Marine Kreatif, 2018)
The Increasing of community needson catfish consumption in West Aceh district is making it more diffucult for catfish farmers tomeet the need. Peunaga Paya Village as one of the catfish producing villages in Meureubo District constrained in meeting the market demand for this product. Not optimal production was one of the causes for that problem.This is due to their knowledge and ability about catfish farming techniques was lacking so their current culture management was still not good. In addition, fish farmers still use conventional technology so they have not understood the importance of adding nutrients in fishfeed to accelerate the harvest period with optimal results. So far, the obstacles they faced are using traditional technology due to lack of partners knowledge and ability, fish susceptible to disease, cultivated fish often experience decreased appetite, poor of water quality, and slow fish growth rate so the harvest time more longerand the cost production increases. In order to solve the problems, it is implemented the community service activities by giving counseling about the proper fish farming techniques and the practice of making probiotics as an additional nutrient to fishfeed withcheap and easy to find ingredients.